URGENSI PEMBAHARUAN HUKUM PIDANA MATERIEL INDONESIA BERDASARKAN NILAI–NILAI KETUHANAN YANG MAHA ESA - Sri Endah Wahyuningsih (Jurnal Pembaharuan Hukum, 2014)
Indonesian criminal law reform material is important because the Criminal Code (WvS) hitherto in force in Indonesia is a Dutch colonial law which includes family/continental legal systems (“Civil Law System”) or “the Romano-Germanic family” were influenced by the teachings of that highlight the concept of “individualism, liberalism and individual rights, so it is not in accordance with the values of Pancasila includes precepts Belief in God Almighty. Thus the need for achange in the sense of reviewing (reorientation and reform) Indonesian criminal law, which is still grounded in the principles and foundations of the philosophy of foreign nations toward the criminal justice system is based on the philosophy of Pancasila as the values of national and state that aspired.